DEVELOPMENT OF DIGITAL MARKETING APPLICATIONS OF CREATIVE ECONOMIC PRODUCTS AND SERVICES IN PADANG CITY WITH E-CRM CONCEPT - Dinul Akhiyar; Irzal Arif Wisky (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2020)
Marketing of creative economy products and services in the city of Padang is currently notintegrated into a single marketing application, it can also be seen that the use of informationtechnology has not been optimal. This research was conducted to develop digital marketingapplications based on the results of marketing analysis of creative economy products and services inthe city of Padang. This research produces knowledge about the conditions and factors thatinfluence the marketing of creative economy products and services in the city of Padang. Thendeveloped a digital marketing application with the concept of electronic customer relationshipmanagement (e-crm), so that it will make it easier for consumers to search, view, compare and maketransactions. so as to increase sales of creative economy products and services in the city ofPadang.